FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI CENGKEH DI DESA WOEWOLO, KABUPATEN NAGEKEO, NUSA TENGGARA TIMUR - Maria Helena Carolinda Dua Mea (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
To plant cloves is very promising for the farmers in Woewolo. The cloves plantation in Woewolo Village, Mauponggo District is an effort to obtain added value for economic life. the purpose of this study was to determine whether capital, labor, and land area affect the production income of clove farmers in Woewolo Village, Nagekeo Regency. This research is a type of quantitative research. The population determined in this study were all clove farmers in Woewolo Village with 75 samples. Primary data collection was carried out by distributing questionnaires to respondents. Based on the Multiple Linear Regression Test the Variables Capital (X1), Labor (X2), and Land Area (X3) have a positive regression coefficient direction on Clove Production in Woewolo Village, Mauponggo District. The statistical test results prove that capital affects clove production as indicated by the acquisition of t-test results, namely the t-count value of 2.452 with a significance of 0.017 at the 5% significance level where 0.017 <0.05. The results of statistical tests prove that labor affects clove production as indicated by the acquisition of t-test results, namely the t-count value of 2.489 with a significance of 0.015 at the 5% significance level where 0.015 <0.05. The results of statistical tests prove that land area affects clove production as indicated by the acquisition of t-test results, namely the t-count value of 5.347 with a significance of 0.000 at the 5% significance level where 0.000 <0.05. the percentage of the contribution of the influence of the independent variables including the capital, labor, and land area on the clove production variable is 35.8%.